0105 Working Memory Impairment Due to Chronic Sleep Restriction, Dose Response to Recovery and Re-Exposure. (27th May 2020) - Kaizi-Lutu, M; Jones, C; Mange, A; Basner, M; Dinges, D F
Abstract: Introduction: Chronic sleep restriction negatively effects working memory. Recovery sleep following sleep restriction partially restores working memory performance. This study examines the impact of chronic sleep restriction and subsequent recovery sleep dose on the N-Back Task (N-Back), a valid measure of working memory. Methods: N=223 participants (29.9±6.9 years; 48.4% female), completed two baseline nights of 8h time in bed (TIB), followed by five nights of 4h TIB, and were then randomized to a sleep dose of 0, 2, 4, 6, 8, 10, or 12 h TIB. A subset of participants (n=73) were re-exposed to another five nights of 4h TIB. Participants completed the three versions of the N-Back (i.e. 1-Back, 2-Back, and B-back) every two hours during wakefulness and daily averages were computed. Mixed effects and linear regression models were used to assess the impact of sleep restriction and the sleep dose response on percent correct on the N-Back corrected for baseline. Results: N=219 participants had valid working memory data. The 2-Back (β =-4.5%; P<0.0001) and the 3-Back (β =-12.5%; P<0.0001) were more difficult than the 1-Back. Working memory performance declined across days of sleep restriction for all N-Backs: 1-Back (β =-1.10%; P<0.0001), 2-Back (β =-0.99%; P<0.0001), and 3-Back (β =-1.10%; P<0.0001). The sleep dose analysis revealed a positive association with N-Back performance for all N-Back versions, 1-Back (β =0.99%; P=0.0002), 2-Back (β =1.46%; P<0.0001), and 3-Back (β =1.43%; P<0.0001). Re-exposure to only one night of 4h TIB following recovery sleep resulted in performance decrements equal to performance prior to recovery sleep for all N-Back versions (Ps>0.41). Conclusion: These data indicate that working memory is adversely impacted by sleep restriction, and that sufficient recovery sleep, possibly across consecutive days, is necessary to maintain optimal working memory performance. Support: Funded by National Institute of Health NIH R01NR004281 and National Space and Biomedical Research Institute NSRBI NCC 5–98